Wear: Achieving Ultralow Wear with Stable Nanocrystalline Metals (Adv. Mater. 32/2018). Issue 32 (6th August 2018) - Curry, John F.; Babuska, Tomas F.; Furnish, Timothy A.; Lu, Ping; Adams, David P.; Kustas, Andrew B.; Nation, Brendan L.; Dugger, Michael T.; Chandross, Michael; Clark, Blythe G.; Boyce, Brad L.; Schuh, Christopher A.; et al.
Abstract : Large‐scale molecular dynamics simulations are used by Nicolas Argibay and co‐workers in article number 1802026 to investigate the stress‐dependent microstructural evolution of highly stable nanocrystalline alloys. They illustrate how an alloy of Pt with 10 at% Au shows suppression of grain growth at high tensile strains, resulting in cohesive failure of grain boundaries as the primary failure mechanism.